Determinan Kecenderungan Fraud Pada BPR Sewilayah kota Semarang - Hayu Estrini, Dwi; Santoso, Tiara Rani; Najmuddin, Ahmad Bebin; Putra Zebua, Fransiskus Selamat (AKUNTANSI DEWANTARA, 2025)
Fraud testing can be evaluated based on several factors, including compensation suitability, organisational culture, anti-fraud awareness, and internal control systems. The primary data was collected through a survey of 146 respondents using a questionnaire given to employees of the People's Credit Bank of Semarang Commissariat. The data was analysed using WarpPLS software. The study found that performance suitability did not significantly affect fraud, while variables related to organisational culture and anti-fraud awareness had a significant impact on fraud. Additionally, testing the internal control system variable as a moderating variable revealed that it was unable to moderate the relationship between anti-fraud awareness and compensation suitability on the tendency to commit fraud. However, the internal control system can moderate the relationship between Organisational Culture and Fraud. This is because employees may face several pressures, opportunities, and rationalisations that can influence their tendency to commit fraud.